Student sensitivity in reading business opportunities during the pandemic - Azizah Husin; Nurfebrianti Nurfebrianti (Sriwijaya University Learning and Education International Journal, 2024)
This study aims to determine the sensitivity of students in reading business opportunities during the pandemic (study of students from the community education study program, Faculty of Teacher Training and Education, Sriwijaya University). This type of research is descriptive with a quantitative approach. Data collection methods used are questionnaires and literature study. The sample of this research is 72 people with a sampling technique that is stratified random sampling. This is evident from seeking information sources, taking advantage of the surrounding environment, interacting with friends, and recognizing business opportunities to determine entrepreneurial readiness. The results showed that students' sensitivity to reading business opportunities during the pandemic was very high. The form of student sensitivity in reading business opportunities based on the attention indicator is classified as very high with a percentage of 84,51%, interest is classified as very high with a percentage of 83.5%, peer environment is classified as high with a percentage of 76.24%, and readiness is classified as very high with a percentage of 82,07%.